PERANCANGAN VIDEO PANDUAN PENGGUNAAN WONDERSHARE FILMORA 12 MENGGUNAKAN BAHASA MELAYU DENGAN MODEL 4D - Bayu Syahputra; Tony Wibowo; Said Teguh Putra Ramadhan (Badan Penelitian dan Pengabdian Masyarakat (BP2M) STMIK Syaikh Zainuddin NW Anjani, 2024)
Video is a series of moving images accompanied by audio to convey information. Video itself is the most popular medium for conveying information today. Information media via video is considered easier to understand and not boring. With increasingly massive technological advances, many foreign cultures have also entered and been implemented by society. As a result, many regional cultures are starting to be abandoned or even forgotten. With the aim of preserving the Malay regional language, which is increasingly fading in the Riau Islands, the author uses Malay as the language of instruction in this video guide. The design of the video guide uses qualitative methods by conducting interviews with quasi-experts and the RnD (Research and Development) method with the 4D model (define, design, development, disseminate). This model is a model used to develop learning tools. At the define stage, the author conducted interviews to dig up information. At the design stage, the writer develops the material obtained in the previous stage into a narrative script and storyboard. In the develop stage the author develops the previous process into a video which will then go through a feasibility and suitability test process by language experts. Then at the disseminate stage, the videos that have been tested are distributed via the YouTube platform.